Federalism and European union : the building of Europe, 1950-2000 - Burgess, Michael, 1949- (Routledge, 2000)
This book demonstrates that a federal Europe is not a serious threat to the survival of the nation-state. Essential reading for all those interested in European federalism, European politics and the history of the EU.